Lattice Numerical Simulations of Hydraulic Fracture Propagation and Their Geometry Evolution in Transversely Isotropic Formations - Qiu, Dezhi; Zhang, Jun; Lin, Yinhe; Liu, Jinchuan; Rabiei, Minou; Rasouli, Vamegh; Damjanac, Branko; Huang, Rui (Frontiers in Earth Science, 2021)
Accurate prediction of the fracture geometry before operation of a hydraulic fracture (HF) job is important for the treatment design. The simplified planar fracture models, which may be applicable to predict the fracture geometry in homogeneous and continuous formations fail in case of fractured reservoirs and laminated formations such as shales. To gain a better understanding of the fracture propagation mechanism in laminated formations and its vertical geometry to be specific, a series of numerical models were run using XSite, a lattice-based simulator. The results were studied to understand the impact of the mechanical properties of caprock and injection parameters on HF propagation. The tensile and shear stimulated areas were used to determine the ability of HF to propagate vertically and horizontally. The results indicated that larger caprock’s Young's modulus increases the stimulated area (SA) in both vertical and horizontal directions, whereas it reduces the fracture aperture. Also, larger vertical stress anisotropy and tensile strength of caprock and natural interfaces inhibits the horizontal fracture propagation with inconsiderable effect in vertical propagation, which collectively reduces the total-SA. It was also observed that increased fluid injection rate suppresses vertical fracture propagation with insignificant effect on horizontal propagation. The dimensionless parameters defined in this study were used to characterize the transition of HF propagation behavior between horizontal and vertical HF.